1981
DOI: 10.1002/nme.1620170103
|View full text |Cite
|
Sign up to set email alerts
|

Some computational aspects of elastic‐plastic large strain analysis

Abstract: SUMMARYThe governing equations for large strain analysis of elastic-plastic problems are reconsidered. An improved form of these equations is derived, which is valid for small increments of strain and large increments of rotation. Special attention is paid to the integration procedures for these equations in the deformation history. It is shown that the tangent modulus procedure for integration of the constitutive equations is conditionally stable, and that implicit methods, such as the 'mean normal' method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(44 citation statements)
references
References 10 publications
1
37
0
6
Order By: Relevance
“…Mogu se koristiti 8-čvorni ili 9-čvorni elementi s 5 ili 6 stupnjeva slobode u svakom čvoru. Šesti stupanj slobode (rotacijska krutost oko normale na srednju plohu ljuske) dodan je prema Kozuliću [8]. Korišteni model materijala ponajprije je namijenjen modeliranju ljuski od konstrukcijskog čelika, uz pretpostavku elastoplastičnog ponašanja [5].…”
Section: Model Za Konstrukcijuunclassified
“…Mogu se koristiti 8-čvorni ili 9-čvorni elementi s 5 ili 6 stupnjeva slobode u svakom čvoru. Šesti stupanj slobode (rotacijska krutost oko normale na srednju plohu ljuske) dodan je prema Kozuliću [8]. Korišteni model materijala ponajprije je namijenjen modeliranju ljuski od konstrukcijskog čelika, uz pretpostavku elastoplastičnog ponašanja [5].…”
Section: Model Za Konstrukcijuunclassified
“…This method is usually referred to as the "1/4" point singularity technique [15]. It is applied by using eight-node quarter of the edge length, and the edge opposite the crack is kept straight.…”
Section: Fracture Mechanicsmentioning
confidence: 99%
“…A mixed isotropic-kinematic hardening model defines subsequent yield surfaces. The Mises yield surface is given by (22) where ts' is the deviatoric part of the shifted stress vector t s , R is the radius of the yield surface in deviatoric stress space, and Ep is the effective plastic strain. R is related to the effective tensile stress Y by (23) The shifted stress ts is given by (24) where t is the current Cauchy stress on the unrotated configuration and tb is the backstress on the unrotated configuration which locates the center of the yield surface (for isotropic hardening, tb = 0).…”
Section: Plasticity Rate Equationsmentioning
confidence: 99%
“…The predicted Cauchy stresses oscillate in an unrealistic manner (a12 actually reverses sign). Nagtegaal and de Jong [22] noted such stress oscillations with kinematic hardening in elasto-plasticityfor a material which strain hardens monotonically in tension. Atluri [2] later showed that similar oscillations exist for isotropic hardening unless the elastic strains are vanishingly small.…”
Section: Introductionmentioning
confidence: 95%